Green-Synthesized Characterization, Antioxidant and Antibacterial Applications of CtAC/MNPs-Ag Nanocomposites - Ayşe Baran; Erdal Ertaş; Mehmet Fırat Baran; Aziz Eftekhari; Zübeyir Gunes; Cumali Keskin; Sergey A. Usanov; Rovshan Khalilov (MDPI AG, 2024)
The emergence of antibiotic resistance, caused by the improper use of antibiotics, is a significant challenge in combating infectious diseases, leading to millions of annual fatalities. The occurrence of antimicrobial side effects catalyzes the investigation of novel antimicrobial compounds and sources of drugs. Consequently, the research on biological activity that is conducted on plants, plant extracts, and compounds that are produced from plant components is of utmost significance. In this study, CtAC/MNPs were obtained by the reaction of activated carbon (AC) obtained from the fruits of the Celtis tournefortii (Ct) plant and magnetic nanoparticles (MNPs), and a CtAC/MNPs-Ag nanocomposite was synthesized by the reduction in silver ions added to the reaction. The synthesized CtAC/MNPs and CtAC/MNPs-Ag nanocomposites were analyzed spectroscopically (FTIR, XRD), microscopically (SEM, EDX), optically (DLS), electrochemically (zeta potential) and magnetically (VSM). The antibacterial activities of CtAC/MNPs and CtAC/MNPs-Ag nanocomposites against S. aureus and E. coli were investigated by microdilution method using minimal inhibitory concentration (MIC) and disk diffusion methods. Antioxidant activity study, including total phenolic content and DPPH and cuprac assays, revealed the remarkable effect of the CtAC/MNPs-Ag nanocomposite. This study has the advantages of obtaining CtAC/MNPs and CtAC/MNPs-Ag nanocomposites in a short time without requiring energy, and most importantly, the reaction takes place without using any toxic substances. In addition, according to the data obtained in the study, the CtAC/MNPs-Ag nanocomposite is thought to shed light on biomedical research.